Climate Resilience or Impeding Vulnerabilities in the Light of Mangroves of Indian Sundarban - Karabi Das; Kanailal Das (Surviving Sundarbans: Tragedy and Hope, Edition 1, 2025)
In this present scenario of climate extremities, both rural and urban communities are facing increasing vulnerabilities. Not only do the coastal communities face the brunt of climate extremities, the future of Kolkata is also at stake. Kolkata has faced the ravages of cyclones Amphan (2020) and the most recent cyclone Remal (2024), while the riparian communities of Indian Sundarbans have faced repeated climate extremities during Aila (2009), Bulbul (2019), Amphan (2020), Yaas (2021) and Remal (2024). The mean sea level shows a long-term rising trend of about 1 mm/yr on an annual average on the Indian coast (Unnikrishnan et al., 2006). Recent observations suggest a rising trend of 2.5 mm/yr. A relative sea level rise of 10-20 mm/yr due to the coupled effects of eustatic sea level and land subsidence is seen in the seaward part of the Bengal delta [1]. Not only climate extremities, but also geomorphic problems have jeopardized the ecosystem of this fragile region. The central sector of the Indian Sundarban is deprived of freshwater due to the siltation of the Bidyadhari River. This has led to the disappearance of sweet water-loving mangroves like Heritiera fomes (Sundari) and Nypa fruticans (Golpata) [2]. Increasing salinity has brought about top dying disease in mangroves which have been protecting this ecosystem over the years. Mangroves act as efficient carbon sink and sequester huge amounts of carbon in their biomass pool (stems, leaves, branches, wood, roots) and sediments. Mangrove species globally can sequester about 4 Gigatons of carbon which are basically accumulated as biomass in both above-ground and below-ground structures [3]. Thus planting mangroves involving community participation has proved as a mitigation strategy for these impeding hazards. This paper relies on the use of quantitative methods like Mann Kendall non-parametric test and Sen’s slope estimator in order to find out the long-term trend of the variable taken, for a period from 1901-2021. Erosion accretion analysis was done using Survey of India toposheets (79C/1, 79C/2 of scale 1:50,000) of 1968 and Landsat 8 image (Path 138, Row 45 and spatial resolution of 30 m) of 2021. Normalized Difference Vegetation Index (NDVI) and Normalized Difference Salinity Index (NDSI) were carried out using QGIS 2.8.9 software to observe vegetation health and salinity. Also, field observations and qualitative surveys of local inhabitants were carried out to chart out a mitigation strategy involving mangroves.